Environmental health ethics - Resnik, David B. (Cambridge : Cambridge University Press, 2012)
"Environmental Health Ethics illuminates the conflicts between prote cting the environment and promoting human health. In this study, David B. Resnik develops a method for making ethical decisions on environment al health issues. He applies this method to various issues, including p esticide use, antibiotic resistance, nutrition policy, vegetarianism, u rban development, occupational safety, disaster preparedness, and globa l climate change. Resnik provides readers with the scientific and techn ical background necessary to understand these issues. He explains that environmental health controversies cannot simply be reduced to humanity versus environment and explores the ways in which human values and con cerns, health, economic development, rights, and justice interact with environmental protection"--Provided by publisher.
Machine generated contents note: -- Introduction -- An overview of e nvironmental health -- Ethical theory -- Toward an environmental health ethics -- Pest control --Genetic engineering, food, and nutrition -- P ollution and waste -- The built environment -- Climate change, energy, and population -- Justice and environmental health -- Environmental res earch involving human participants -- Conclusion.
Includes bibliographical references and index.
Keywords: Environmental Health -- ethics; Environmental Medicine -- ethics; Environmental policy; Environmental Pollution -- ethics; Environment health